Association between residential greenness and all-cause mortality and the joint mediation effect of air pollutants among old people with disability: A prospective cohort study - Feng, Chuanteng; Yu, Bin; Fei, Teng; Jia, Peng; Dou, Qingyu; Yang, Shujuan (The Science of the total environment, 2023)
Residential greenness offers health benefits to old people, but evidence of its association with the health of old people with disability is scarce. Moreover, due to the limited mobility of this vulnerable population, air pollutants may play an indispensable mediating role in that association, which however remains understudied. This study aimed to investigate the association between residential greenness and all-cause mortality risk and the joint mediation effect of air pollutants among old people with disability. A total of 34,075 old people with disability were included in the Chengdu Long-term Care Insurance cohort. Participants' residential greenness exposure was measured by an enhanced vegetation index within the 500 m buffer zone (EVI500m). Causal mediation analysis was conducted to assess the total effect (TE) of residential greenness and the natural indirect effect (NIE) through PM2.5, CO, NO2, SO2, and O3 on all-cause mortality. The TE of EVI500m on the all-cause mortality risk in overall participants showed negative, which, decreased from the 2nd quartile (HR = 0.93, 95 % CI: 0. 91, 0.95) to the 4th quartile (HR = 0.81, 95 % CI: 0.76, 0.85); the NIE through the five air pollutants also decreased from the 2nd quartile (HR = 0.96, 95 % CI: 0.95, 0.98) to the 4th quartile (HR = 0.90, 95 % CI: 0.88, 0.93), with the proportion mediated decreased from 48 % to 44 %. The stronger TE or NIE were observed in participants aged <80 years old, men, with mild-moderate disability, and having outdoor experience every week. Exposure to residential greenness was associated with a decreased risk of mortality, partially through the pathways of air pollutants, which varied by age, sex, degree of disability, and frequency of weekly outdoors. Our findings would provide evidence to develop aging-friendly cities. [Display omitted] •Higher exposure to residential greenness was associated with a lower risk of mortality among old people with disability.•PM2.5, NO2, CO, SO2 and O3 played a mediating role in greenness-mortality pathway.•The maximum joint mediation effect of PM2.5, NO2, CO, SO2 and O3 was as high as 48 %.•Old people <80 years old, men, with mild-moderate disability and having outdoor experience benefited more from greenness.